Morpho-Physiological Responses of Purbalingga and Purowkerto Local Black Rices to Drought Stress - Ummi Sholikhah; Khusna Khamidah; Tri Handoyo; Ahmad Ilham Tanzil; Wahyu Indra Duwi Fanata; Tri Ratnasari; Tri Wahyu Saputra (The University of Lampung, 2025)
Black rice (Oryza sativa L. indica) is a pigmented rice plant that has high antioxidant content. Drought is an abiotic stress that can inhibit the growth and productivity of rice plants. Planting of local black rice with several drought treatments using PEG 6000 was observed in this study. The aim of this research is to determine the morphological and physiological response of local black rice plants in Purbalingga and Purwokerto at various levels of drought stress. This research used a Completely Randomized Design (CRD) with 2 factors. The first factor is 2 local black rice plants, namely Purbalingga and Purwokerto. The second factor was drought stress treatment via PEG 6000 with 4 treatments, namely 0% PEG (control), 5%, 10%, and 15%. The results showed that when applying 15% PEG, local black rice in Purbalingga and Purwokerto experienced a decrease in plant height and number of leaves but increased root length. Based on the physiological response, when addition 15% PEG there was a decrease in the amount of chlorophyll and an increase in the content of H2O2 and anthocyanins in both Purbalingga and Purwokerto local black rice. Keywords: Black Rice, Drought Stress, Morphological Response, Physiological Response.